Relationship between Sexual Attitude, Quality of Life and Couple Satisfaction in Unmarried Young Adults - Akansha Mahalwal; Dr. Kamini C. Tanwar; Dr. Lokesh Gupta (International Journal of Indian Psychȯlogy, 2022)
Couple satisfaction is influenced by many aspects which are part of human daily living, but this study focus on sexual attitude and quality of life in today’s generation. Societal acceptance is not modernize on openly talking about sex, sexual habits, attitude and judging committed couples. The focus is to deliver a different perspective in society to normalize on the same as not an issue but something which is essential for one to learn and grow. The present study is conducted to assess the relation between sexual attitude, quality of life and couple satisfaction in unmarried young adults as well as to find out differences in male & females on all three variables. The sample is based on 110 university students both males and females of Delhi- NCR region using the tools Brief Sexual Attitude Scale (Hendrick & Hendrick, 1987), WHO Quality of Life (1995) and Couple Satisfaction Index (Funk and Rogge, 2007). The sample represents 55 males and 55 females of age group (18-30 years) who are unmarried university students, committed in a relationship. Pearson correlation & t-test was applied to find out the result. The analysis reveals an insignificant correlation between sexual attitude, quality of life and couple satisfaction. Men displays a higher rate of sexual attitude, sexual habit and couple satisfaction when compared against women.